Дослідження режимів роботи тепловоза ЧМЕ3 на імітаційній моделі - Буряковький, С.Г.; Маслій, А.С.; Панченко, В.В.; Помазан, Д.П.; Деніс, І.В. (Електротехніка і електромеханіка, 2018)
Розроблено імітаційну модель тепловоза ЧМЕ3, шо складається з дизеля з регулятором кількості обертів колінчастого валу,
тягового генератора постійного струму незалежного збудження та тягового електричного приводу. Проведене тестування
роботи імітаційної моделі на профілі ділянки шляху Харків - Мерефа, при цьому основними обмеженнями є час руху, який для
даного перегону не повинен перевищувати 45 хв., а також максимальна допустима швидкість, яка для вантажних потягів
складає 80км/год. Отримана тривимірна поверхня, що показує залежність витрат палива локомотива від режиму ведення
потяга машиністом при виконанні однакової роботи, тобто однакового часу руху по перегону. Разработана имитационная модель тепловоза ЧМЭ3, которая состоит из дизеля с регулятором числа оборотов коленчатого вала, тягового генератора постоянного тока независимого возбуждения и тягового электрического привода. Проведено тестирование работы имитационной модели на профиле участка пути Харьков - Мерефа, при этом
основными ограничениями являются время движения, для данного перегона не должно превышать 45 мин., а также
максимальная допустимая скорость, которая для грузовых поездов составляет 80км/ч. Получена трехмерная поверхность, которая показывает зависимость расхода топлива локомотива от режима ведения поезда машинистом при
выполнении одинаковой работы, то есть одинакового времени движения по перегону. Introduction. Fuel consumption by diesel locomotive during operation depends significantly on many factors, among which the
main is the mode of driving a train. Purpose. Research on the
mathematical model of the modes of driving a train on the site of
Kharkiv-Merefa with the purpose of the main oscillograms of the
operation of the locomotive on the site. Methodology. A mathematical model of the operation of the main units of the locomotive
CHME3 in the Matlab environment was developed. The model of
the diesel engine is based on the calculated indicator diagram of
its operation, which is approximated by a continuous dependence.
The control panel operates on a system of conditions, the purpose
of which is to maintain the set speed. Results. In the course of the
simulation, statistical data were obtained on the fuel consumption
of the diesel locomotive when it operated on a section with a train
of constant mass. Based on the data obtained, a three-dimensional
surface is constructed showing the dependence of the fuel consumption on the time of the site's exploration and the maximum
speed on the site. Practical value. The dependence obtained can
be used to optimize the driving behavior of trains along a section.
The apparent dependence of fuel consumption on the driver's
behavior is the basis for the further development of automatic
locomotive speed control systems